Today I learned that, for 2 positive integers a and b , g cd ( a , b ) × lcm ( a , b ) = a × b . Can we extend this formula to 3 positive integers as follows: g cd ( a , b , c ) × lcm ( a , b , c ) = a × b × c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
To prove that the answer is No we just need a counter-example
Just pick a = b = c = 1 :
g cd ( a , b , c ) = g cd ( a , a , a ) = a
l c m ( a , b , c ) = l c m ( a , a , a ) = a
g cd ( a , b , c ) ⋅ l c m ( a , b , c ) = a ⋅ a = a 2 = a 3 = a ⋅ b ⋅ c
Problem Loading...
Note Loading...
Set Loading...
Intuition behind g cd ( a , b ) lcm ( a , b ) = a b is that a and b are expressed as products of their prime factors with corresponding exponents and in g cd ( a , b ) we take the smaller exponent between a and b for every prime and in lcm ( a , b ) the larger.
This means that the left side contains a product of primes with exponents being the smaller exponents multiplied by a product of primes with exponents being the larger exponents, but on the right side we have them shuffled between a and b .
Since, multiplication is commutative, the both sides of the equation have the same value.
However, for 3 positive integers, there is no similar formula because by taking the smallest exponents with g cd and largest exponents with lcm we have no way of taking the middle exponent into account.
This means that the formula above only works if the middle exponents are all 0 , meaning that the smallest exponents are also 0 and largest are whatever we want.
Hence, g cd ( a , b , c ) lcm ( a , b , c ) = a b c is true iff two of the positive integers are 1 .